On the Periods of Parallel Dynamical Systems - Juan A. Aledo; Luis G. Diaz; Silvia Martinez; Jose C. Valverde (Complexity)
In this work, we provide conditions to obtain fixed point theorems for parallel dynamical systems over graphs with (Boolean) maxterms and minterms as global evolution operators. In order to do that, we previously prove that periodic orbits of different periods cannot coexist, which implies that Sharkovsky’s order is not valid for this kind of dynamical systems.